Enzyme-free glucose sensor based on ferrite magnetic nanoparticles / Zohreh Shahnavaz - Zohreh, Shahnavaz (2016)
Magnetic nanoparticles have gained great interest recently due to their unique properties which stood up as the candidate constructing novel sensing devices; particularly in electrochemical sensors. The main goal of this research is to develop a sensitive enzyme-free glucose sensor based on nanocomposite comprises of magnetic nanoparticles, embedded in polymer matrix or graphene oxide. This is accomplished by preparation of four types of nanocomposites, namely polypyrrole (PPy) coated copper iron oxide (CuFe2O4/PPy), polypyrrole coated zinc iron oxide (ZnFe2O4/PPy), copper iron oxide reduced graphene oxide (CuFe2O4/rGO) and zinc iron oxide reduced graphene oxide (ZnFe2O4/rGO). The morphology and surface property of coating phenomenon of prepared nanocomposites were examined by Transmission Electron Microscopy (TEM), Scanning Electron Microscopy (SEM), X-ray Diffraction (XRD) and Fourier Transform Infrared (FTIR). In the first two mentioned composites, SEM and TEM images displayed the spherical shape of CuFe2O4 and ZnFe2O4 nanoparticles with diameters ranging from 20 to 90 nm. The XRD and FTIR analyses confirmed that CuFe2O4 and ZnFe2O4 nanoparticles served as the nucleation sites for the polymerization of pyrrole as there is no chemical interaction between them. For the other two nanocomposites which were modified with reduced graphene oxide, SEM and TEM images showed the dispersion of magnetic nanoparticles on the graphene nanosheets which pre-synthesized via hydrothermal method. This finding is further confirmed by XRD and FTIR which supported the reduction of GO and the presence of ZnFe2O4 and CuFe2O4 nanoparticles which distributed within the graphene sheets. The sensor performance based on CuFe2O4/PPy nanocomposite showed a highly active electrochemical surface area and a fascinating electro-catalytic activity for the glucose oxidation. In the amperometric detection of glucose, CuFe2O4/PPy nanocomposite modified glassy carbon electrode exhibited detection limit and sensitivity of 0.1 μM and